THE ROLE OF MATHEMATICS IN ELEMENTARY CLASSES - Alijonov Sirojiddin Husan oʻgʻli; Khabibullaev Sherozbek Khamidulla o'g'li; Tokhtaev Zakirjon Abidovich; Usmonov Isroiljon Muxtorjon o'g'li (American Journals, 2023)
In this article, the role of mathematics in primary grades, Problem Solving and Critical Thinking Skills, Logical Reasoning and Communication Skills.
Keywords: Primary grades, Mathematics, structure, patterns, engineering, medicine, calculation, skills.